The Phosphate Fast-Responsive Genes PECP1 and PPsPase1 Affect Phosphocholine and Phosphoethanolamine Content . Issue 4 (23rd February 2018) - Hanchi, Mohamed; Thibaud, Marie-Christine; Légeret, Bertrand; Kuwata, Keiko; Pochon, Nathalie; Beisson, Fred; Cao, Aiqin; Cuyas, Laura; David, Pascale; Doerner, Peter; Ferjani, Ali; Lai, Fan; et al.
Abstract : Intense induction of PPsPase1 and PECP1 phosphatases impacts phosphocholine and phosphoethanolamine content in Arabidopsis. Abstract: Phosphate starvation-mediated induction of the HAD-type phosphatases PPsPase1 (AT1G73010) and PECP1 (AT1G17710) has been reported in Arabidopsis ( Arabidopsis thaliana ). However, little is known about their in vivo function or impact on plant responses to nutrient deficiency. The preferences of PPsPase1 and PECP1 for different substrates have been studied in vitro but require confirmation in planta. Here, we examined the in vivo function of both enzymes using a reverse genetics approach. We demonstrated that PPsPase1 and PECP1 affect plant phosphocholine and phosphoethanolamine content, but not the pyrophosphate-related phenotypes. These observations suggest that the enzymes play a similar role in planta related to the recycling of polar heads from membrane lipids that is triggered during phosphate starvation. Altering the expression of the genes encoding these enzymes had no effect on lipid composition, possibly due to compensation by other lipid recycling pathways triggered during phosphate starvation. Furthermore, our results indicated that PPsPase1 and PECP1 do not influence phosphate homeostasis, since the inactivation of these genes had no effect on phosphate content or on the induction of molecular markers related to phosphate starvation. A combination of transcriptomics and imaging analyses revealed that PPsPase1 and PECP1 display a highly dynamic expression pattern that closely mirrors the phosphate status. This temporal dynamism, combined with the wide range of induction levels, broad expression, and lack of a direct effect on Pi content and regulation, makes PPsPase1 and PECP1 useful molecular markers of the phosphate starvation response.